SYNTHESIS OF FRACTAL ANTENES IN THE PACKAGE MMANNA (Modern information system and technologies, 2018)
The results of simulation of antennas on fractal basis are presented in the work. Due to the complexity of describing the interaction of non-Euclidean geometry antennas with radio waves, their synthesis was performed using the MMANA-GAL program. The proposed sequence of simulation steps allows for multi-bandwidth and broadband. On the basis of the conducted researches recommendations on practical application of fractal structures in the interests of systems and networks 802.11х and 5G are offered.